2018
DOI: 10.1007/978-3-319-73915-1_42
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Outerplanarity

Abstract: We study straight-line drawings of graphs where the vertices are placed in convex position in the plane, i.e., convex drawings. We consider two families of graph classes with nice convex drawings: outer k-planar graphs, where each edge is crossed by at most k other edges; and, outer k-quasi-planar graphs where no k edges can mutually cross. We show that the outer k-planar graphs are ( √ 4k + 1 + 1)-degenerate, and consequently that every outer k-planar graph can be ( √ 4k + 1 +2)colored, and this bound is tigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Convex geometric k-planar graphs in which all the vertices form a simple cycle can be recognized in linear time, because they can be expressed in extended monadic second-order logic and have bounded threewidth. In [73] we can also find families of 3-quasi planar graphs that are convex geometric and families that are not convex geometric.…”
Section: Vertices On Lines Circles and External Boundarymentioning
confidence: 97%
See 2 more Smart Citations
“…Convex geometric k-planar graphs in which all the vertices form a simple cycle can be recognized in linear time, because they can be expressed in extended monadic second-order logic and have bounded threewidth. In [73] we can also find families of 3-quasi planar graphs that are convex geometric and families that are not convex geometric.…”
Section: Vertices On Lines Circles and External Boundarymentioning
confidence: 97%
“…Note that, the edge crossings in a geometric graph with all vertices in convex position are the same as the edge crossings of a 1-page drawing in which the order of the vertices along the spine is the same as the circular order of the vertices on the convex polygon. Several interesting properties of convex geometric k-planar and k-quasi planar graphs have been recently investigated [73]. It is shown that convex geometric k-planar graphs are √ 4k + 1 +1-degenerate and consequently √ 4k + 1 + 2-colorable.…”
Section: Vertices On Lines Circles and External Boundarymentioning
confidence: 99%
See 1 more Smart Citation
“…Seemingly the only min-saturation results involving this crossing restriction concern so-called outer or convex drawings in which all of the vertices occur on the boundary of a single face of the drawing. Here, as in planar drawings, the min-saturated drawings and max-saturated outer k-quasiplanar n-vertex drawings coincide [12,14,25], and have 2(k − 1)n − 2k−1 2 edges [11]. Also for the concept of gap-planarity [7], which generalizes the notion of k-planarity, the focus so far has been on the Turán-type question.…”
Section: Related Workmentioning
confidence: 99%
“…To prove our main result (Theorem 2) we develop an algorithm that tests whether bc • (G) = k in FPT time with respect to k. Our algorithm is inspired by recent works on circular layouts with at most k crossings [3] and circular layouts where each edge is crossed at most k times [4]. In both of these prior works, it is first observed that the graphs admitting such circular layouts have treewidth O(k), and then algorithms are developed using Courcelle's theorem, which establishes that expressions in MSO 2 logic can be evaluated efficiently.…”
Section: Fpt Algorithms For Computing Bc • (G) and Bc • (G)mentioning
confidence: 99%